Child’s resilience in face of maltreatment: A meta-analysis of empirical studies - Nasvytienė, Dalia; Lazdauskas, Tomas; Leonavičienė, Teresė (Psichologija, 2012)
The growing field of empirical studies on child’s resilience encouraged us to conduct a meta-analysis in order to integrate the findings across studies targeted at child’s adaptive functioning after experiences of maltreatment. In face of substantial and unbiased empirical evidence (published in scientific databases before 2010), research questions were raised about extant verifiable explanatory knowledge as well as implications for countries just starting such research. Domain-specific resources accounted for the majority of attributes of resilience. The aim of the study was to investigate the attributes of a child’s positive functioning in face of maltreatment. We used the Comprehensive Meta-Analysis V2 software program and applied the guidelines for psychometric meta-analysis. Attributes of resilience were treated as moderator variables and assigned to one of three categories according to the framework of the study, namely, individual characteristics (classified through the domains of child cognition, self-perception and temperament / personality traits), characteristics of Interpersonal relatedness (domain of close relationships within family, domain of relations outside family, i. e. connectedness with peers and other competent adults), and characteristics of Community. Our findings suggest that a child’s individual characteristics are somewhat more related to resilience than his / her interpersonal relations or the setting of a community network. The overall effect sizes are small, the total number of participants is 19 300. Empirical evidence does not support the linear increase of resilience with the child’s age. At present, the measurement is of crucial importance for studies of resilience considered as a dynamic characteristic of functioning. In the studies of early childhood development, it is difficult to differentiate between correlates of post facto resiliency outcomes and attributes of age-appropriate positive functioning. Statements can be made only with regard to the overall quality of life of a child.